(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Craniocerebral trauma in children appears to many parents as a head wound after a very severe accident or accident. In reality, however, it even includes a concussion or mild brain contusion, as well as pediatric shaken baby syndrome. A child can be injured on a walk, while playing or exploring the world around them, or through the fault of adults in abusive or simply unreasonable treatment. Head injuries require increased attention because of the frequent development of delayed cognitive impairment, which is accompanied by neurological symptoms. Children may face difficulties after suffering a disorder